The role of student writing in learning in zoology - Moore, Robin Stanley (Rhodes University, Faculty of Education, Department of Education, 1996)
In this study I attempt to develop a rationale for the role of student writing in advancing learning in Zoology. To this end, I use the informed and insightful voices of five academics from the University of Cape Town's Department of Zoology to present a picture of the goals of the discipline, how they view the role that student writing plays in advan~ing these goals, a sense of the tensions they face in dealing with student diversity, and the promise and challenges of innovative approaches. My interest in how staff view student writing stems from a belief that staff make use of student writing in different ways, depending on their assumptions about writing. I explore these assumptions by means of interviews with members of staff, in which I ask about how they understand the pursuit of science, the qualities a scientist needs to develop, the best ways to develop these qualities in students, and the part that student writing plays in this development. What emerges in this study is the understanding that the kinds of writing we ask students to do reflect the forms of educational practice that we sustain. On the one hand, certain forms of writing may support forms of transmission pedagogy that are viewed as being at odds with progressive science education. On the other hand, if we are to develop alternative teaching approaches which are in keeping with contemporary views of science and learning, then we need to develop new genres of student writing that give expression to these goals and methods. The study concludes with suggested avenues into curriculum review that would operationalise the insights developed by this study.
Keywords: Zoology -- Study and teaching; Communication in science -- Study and teaching; Science -- Study and teaching